STRATEGI DIFERENSIASI DALAM MENINGKATKAN KEUNGGULAN BERSAING DI KECAMATAN LECES KABUPATEN PROBOLINGGO (Jurnal Bisnis Indonesia, 2022)
The industrial sector is an economic sector that provides jobs for the community by converting raw materials into goods that have more value. With the existence of the industrial sector in Indonesia, it helps improve the economy and development of the country for a better future. One that is included in the industrial sector is the furniture industry. The furniture industry is an industry that processes raw materials from wood or rattan into finished goods that have interior designs and artistic values ​​that can provide comfort so that they can support consumer activities. This industry has an important role for consumers because it will continue to be needed and used at any time. . The results of the study by partially testing that the differentiation strategy has a positive and significant effect on competitive advantage. The differentiation strategy carried out by the Micro, Small and Medium Enterprises (MSMEs) in the furniture industry in Leces District, Probolinggo Regency has been quite well implemented. This can be seen from the dimensions of the differentiation strategy responded by the owners or leaders of the furniture industry MSMEs, which researchers can interpret that the differentiation strategy carried out by the company is good and has already been realized with many respondents' answers stating that they agree, although there are still a few shortcomings and doubts from one of them. One application of the dimension of differentiation strategy carried out by MSMEs in the furniture industry in Leces District, Probolinggo Regency that needs further attention. DOI : https://doi.org/10.33005/jbi.v13i1.3080